"Beauty" Based on the Functionality of Smart Skin in Buildings. Issue 4 (1st December 2017) - Al-Dın, Salar Salah Muhy; Nia, Hourakhsh Ahmad
Abstract : The aim of this study is to extend the rationale and comprehensive understanding in respect of the notion of functionality and beauty in the smart skin buildings. Smart skin in buildings plays a key role in improving building functionality, and the future lies in the use of innovative smart skin strategies. The methodology focused on the objectivity and subjectivity of human perception to assess the aesthetic value of a building's smart skin. A theoretical analysis has been conducted based on the results of the investigation model and fortified by comparing the results with the findings obtained through the opinions of experts based in AHP methodology. The study demonstrates that there is a relation between both the aesthetic value and the functionality of the smart skin of a building. The findings revealed the difference in the aesthetic evaluation between the subjective functionality and the objective functionality of the building skin. The findings contribute useful evidence for the promotion of our understanding regarding the aesthetic value of the smart skin of a building, based on its functionality.